LATE-HOLOCENE CATASTROPHIC FLOODS IN THE TERMINAL ARNO RIVER (PISA, CENTRAL ITALY) FROM THE STORY OF A ROMAN RIVERINE HARBOUR - Benvenuti M.; Mariotti-Lippi M.; Pallecchi P.; Sagri M. (My University, 2006)
The results of the stratigraphic and sedimentological analysis carried out at an exceptional archaeological site situated in the coastal plain of the Arno and Serchio Rivers (western Tuscany, Italy) are reported. The site, discovered near central Pisa, records a 1000-yr history of a riverine harbour built by the Etruscans and used by the Romans. This harbour was adjacent to the Arno River, located within an abandoned channel then still connected to the sea, thus allowing efficient stock transfer to and from Roman Pisa. The archaeological importance of this site is primarily due to the discovery of at least 16 well-preserved Roman ships and many other remains mostly deriving from their cargoes. The sedimentological relevance of this record is related to the recurrent, catastrophic, destruction of the harbour documented by the features of the sediment encasing the ships and by the ships’ distribution and age. Such repeated destruction was related to catastrophic flood flows generated by levee crevassing of the Arno River during high-magnitude floods that occurred between the second century BC and the fifth century AD. The Pisa harbour tells a story of river channel instability. The repeated flooding of the harbour indicates that the Roman Arno River attempted to abruptly change its course, exploiting a pre-existing river channel. The concomitance of climatic and eustatic causes is expounded upon to explain the sedimentary dynamic of a coastal floodplain during historical times.
Keywords: LATE HOLOCENE; ARNO RIVER FLOODPLAIN; ROMAN HARBOUR; CATASTROPHIC FLOODS; RIVER CHANNEL INSTABILITY; ITALY; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен